The reconstruction of academic identity through language policy: a narrative approach. Issue 3 (2nd September 2021) - ALKhatib, Hadeel; Romanowski, Michael H.; Du, Xiangyn; Cherif, Maha
ABSTRACT: This article aims to examine how language policy affects the reconstruction of academic identities in a time of rapid and significant changes in contemporary higher education. Through a narrative approach, we explore how a top-down language policy chaperones the process of redefining the perceptions of our positions as academic faculty working at Qatar University, recognized as the world's most international university. Three main themes emerged from data analysis: language identities; narratives of exclusion and self-exclusion; and working in a Third Space. We conclude that the linguistic status quo poorly serves university staff in contemporary higher education and maintain that language policies must be aligned with, and better reflect, the sociolinguistic realities of university life in a global era.